Efektivitas Penerapan Desain Instruksional Archerys Id Model Terhadap Pemahaman Etika dan Kinerja Siswa dalam Pembelajaran Informatika di SMP Pertiwi 2 Padang - Maharani, Wury; Darmansyah, Darmansyah; Rahmi, Ulfia; Kurnia, Reni (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to test the effectiveness of the Archerys ID Model learning design in improving students' understanding of ethics and performance in informatics learning in grade VIII of SMP Pertiwi 2 Padang. The problems identified were low motivation and student performance due to monotonous learning methods and lack of confidence. This study uses mixed methods with quantitative data collection through pretest-posttest and questionnaire, as well as qualitative data through observation and interviews. This study involved grade VIII students who were randomly divided into two groups, namely the experimental group and the control group. The experimental group was taught using the Archerys ID model, while the control group used conventional learning methods. The results of quantitative data analysis showed a significant improvement in students' understanding of ethics and performance after the application of the Archerys ID model. Thus, it can be concluded that the Archerys ID Model learning design is effective in improving ethical understanding and student performance in informatics learning